Semantic and syntactic aspects of the modal verb ‘ameaçar’ - Ferreira, Luiz Fernando; Rech, Núbia Ferreira (Cadernos do IL, 2026)
The verb ameaçar originally means to intimidate, however, in Brazilian Portuguese, it has also developed a second meaning indicating possibilities which was not previously described in the literature. This paper’s goal is to provide a semantic and syntactic analysis of ameaçar’s modal use following formal semanticsand cartographic syntax. We have gathered and analyzed one hundred naturalistic data of ameaçar’s modal use from the Portuguese Corpus and also negative data using the introspective method. We assume that, semantically, ameaçar indicates that the actual world w is on the verge of becoming a possible world in which p is true and, syntactically, it is an unacusative lexical verb.